HPV Screening as an Alternative to Pap Smear in Cervical Cancer Prevention: A Comparative Study in North India - Eric Kwasi Elliason; Atul Khajuria; Stephen Monday; J. Samuel Kamanda (International Journal of Women's Health Nursing And Practices, 2025)
Cervical cancer remains a leading cause of cancer-related morbidity and mortality among Indian women, especially in low-resource settings. While Pap smear testing has been the standard screening method, HPV DNA testing offers potential advantages in sensitivity, cost-effectiveness, and feasibility for large-scale implementation. This study compares the efficacy, cost, and acceptability of HPV screening versus Pap smears in urban and rural populations of North India. A comparative cohort study was conducted among 1,250 women (625 urban, 625 rural), aged 18 years and above, recruited through stratified random sampling across North India. Participants underwent both HPV DNA testing and Pap smears. Data on diagnostic performance, cost per detection and prevention, and acceptability were gathered through structured questionnaires and laboratory analysis. Statistical methods included descriptive analysis, chi-square tests, and logistic regression. HPV screening demonstrated higher sensitivity (93 vs. 85%) but slightly lower specificity (85 vs. 92%) compared to Pap smears. It was also more cost-effective, with lower costs per detection (₹800–1,200 vs. ₹1,500–3,000) and prevention (₹2,500–3,500 vs. ₹4,000–6,000). Urban women reported greater acceptability (HPV: 85%; Pap: 90%) than rural women (HPV: 65%; Pap: 75%), with rural hesitancy attributed to cultural barriers and privacy concerns. Screening participation was higher in urban areas (90 vs. 75%), influenced by healthcare access and educational levels. In conclusion, HPV testing is a more sensitive and cost-effective alternative to Pap smears, particularly suitable for resource-limited rural settings. Public health efforts should prioritize HPV-based screening, supported by community education and mobile outreach to reduce cervical cancer disparities.
Keywords: HPV screening; cervical cancer; cost-effectiveness; pap smear; rural health disparities